Optimizing tourism development using Google Trends and nighttime light (NTL) data - Kartiasih, Fitri; Azhari, Azhari; Rinangku, Rahadian Eka Bagus Indra (Jurnal Ekonomi Indonesia, 2025)
Tourism plays a strategic role in driving regional economic growth through job creation, cultural preservation, and equitable development. East Java Province recorded the highest number of domestic tourist visits in 2024; however, not all districts and cities have received digital exposure and infrastructure support proportional to their tourism potential. This study analyzes digital visibility, infrastructure development, and tourist arrivals across 38 districts and cities, and classifies them using descriptive analysis, Pearson correlation, and K-Means Clustering. Data sources include Google Trends (digital tourism interest), Nighttime Light imagery (infrastructure development), and domestic tourist statistics from BPS. The results identify four clusters with distinct characteristics, with Surabaya City showing high performance in all aspects, while other regions demonstrate strong digital interest but limited infrastructure. The study recommends targeted digital promotion, infrastructure enhancement for high-demand destinations, and strengthened tourism attractiveness in emerging areas, contributing to more efficient, inclusive, and sustainable tourism development.